Contribution of S100A4-expressing fibroblasts to anti-SSA/Ro-associated atrioventricular nodal calcification and soluble S100A4 as a biomarker of clinical severity - Firl, Christina E. M.; Halushka, Marc; Fraser, Nicola; Masson, Mala; Cuneo, Bettina F.; Saxena, Amit; Clancy, Robert; Buyon, Jill (Frontiers in Immunology, 2023)
Background: Fibrosis and dystrophic calcification disrupting conduction tissue architecture are histopathological lesions characterizing cardiac manifestations of neonatal lupus (cardiac-NL) associated with maternal anti-SSA/Ro antibodies. Objectives: Increased appreciation of heterogeneity in fibroblasts encourages re-examination of existing models with the consideration of multiple fibroblast subtypes (and their unique functional differences) in mind. This study addressed fibroblast heterogeneity by examining expression of α-Smooth Muscle Actin (myofibroblasts) and of S100 Calcium-Binding Protein A4 (S100A4). Methods: Using a previously established model of rheumatic scarring/fibrosis in vitro, supported by the examination of cord blood from cardiac-NL neonates and their healthy (Ro-exposed) counterparts, and autopsy tissue from fetuses dying with CHB the current study was initiated to more clearly define and distinguish the S100A4-positive fibroblast in the fetal cardiac environment. Results: S100A4 immunostaining was observed in 4 cardiac-NL hearts with positional identity in the conduction system at regions of dystrophic calcification but not fibrotic zones, the latter containing only myofibroblasts. In vitro, fibroblasts cultured with supernatants of macrophages transfected with hY3 (noncoding ssRNA) differentiated into myofibroblasts or S100A4+ fibroblasts. Myofibroblasts expressed collagen while S100A4+ fibroblasts expressed pro-angiogenic cytokines and proteases that degrade collagen. Cord blood levels of S100A4 in anti-Ro/SSA exposed neonates tracked disease severity and, in discordant twins, distinguished affected from unaffected. Conclusions: These findings position the S100A4+ fibroblast alongside the canonical myofibroblast in the pathogenesis of cardiac-NL. Neonatal S100A4 levels support a novel biomarker of poor prognosis.